2017
DOI: 10.1002/jclp.22554
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the distress tolerance scale‐short form in obsessive compulsive disorder

Abstract: The DTS-SF was found to be a valid and reliable measure with high clinical utility for quickly and accurately measuring DT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 47 publications
6
23
0
Order By: Relevance
“…Firstly, a brief measure of distress tolerance was used to reduce respondent burden at admission. However, the four-item scale showed a satisfactory single-factor structure, and short-form measures have shown acceptable performance in prior research (Garner et al, 2018;Veilleux et al, 2018). The low burden to participants is particularly useful for integration into comprehensive cross-sectional assessments and routine monitoring programs.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Firstly, a brief measure of distress tolerance was used to reduce respondent burden at admission. However, the four-item scale showed a satisfactory single-factor structure, and short-form measures have shown acceptable performance in prior research (Garner et al, 2018;Veilleux et al, 2018). The low burden to participants is particularly useful for integration into comprehensive cross-sectional assessments and routine monitoring programs.…”
Section: Discussionmentioning
confidence: 97%
“…Four items were taken from the Distress Tolerance Scale (Simons & Gaher, 2005) to measure emotional and behavioral tendencies in response to distressing events. Selection of these items were informed by recent research from Garner et al (2018), who found four items showed an acceptable single‐factor structure in clinical and non‐clinical samples: (1) “My feelings of distress are so intense that they completely take over”; (2) “Being distressed or upset is always a major ordeal for me”; (3) “I can't handle feeling distressed or upset”; (4) “I'll do anything to stop feeling distressed or upset”. These items tapped into the four distress tolerance components proposed by Simons and Gaher (2005), such as tolerance, appraisal, absorption, and regulation.…”
Section: Methodsmentioning
confidence: 99%
“…A four-item Distress Tolerance Scale – Short Form (DTS; Garner et al, 2018) was used to assess individuals’ perceived ability to withstand negative affect. The four items measured distinct factors, including distress tolerance (e.g., “I cannot handle feeling distressed or upset.”).…”
Section: Methodsmentioning
confidence: 99%
“…Distress Tolerance. Distress tolerance, an individual's perceived ability to experience and endure negative psychological states, was assessed with the Distress Tolerance Scale-Short Form (DTS-SF; Garner et al, 2018), a self-report of overall distress tolerance with four 5point Likert items ranging from 1 (strongly agree) to 5 (strongly disagree). The DTS-SF is a subset of the items from the 15-item Distress Tolerance Scale (DTS; Simons & Gaher, 2005) with the highest factor loadings from each of the original DTS subscales (Leyro et al, 2011): tolerance, appraisal, absorption, and regulation.…”
Section: Trait-level Moderatorsmentioning
confidence: 99%